INTEGRASI PENDIDIKAN NILAI DALAM PEMBELAJARAN ANAK SEKOLAH DASAR DI ERA REVOLUSI INDUSTRI 4.0 - Akhirunnisa Hasibuan; Yakobus Ndona; Daulat Saragih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Industrial Revolution 4.0 era has brought fundamental transformations in education through digitalization and global connectivity. While providing broader access to learning, this era poses the risk of moral degradation and reduced meaningful social interaction. This study analyzes strategies for integrating values ​​education into elementary school learning in the digital era using a library research method. The results indicate that the integration of values ​​education is a necessity so that technological advances do not distance the younger generation from the nation's noble values. The PAIKEM (Active, Innovative, Creative, Effective, and Enjoyable Learning) model effectively integrates five core values: religious, nationalist, independent, mutual cooperation, and integrity, with teachers as facilitators and role models. Implementation challenges include a lack of teacher understanding, limited infrastructure, and minimal environmental support. The solution is through synergistic collaboration between families, schools, and the community. This research contributes to the development of Indonesian education in producing a generation that is intellectually and technologically intelligent and possesses strong character in the digital era